Law Enforcement Against Gambling Crime in Gorontalo City Police Area - Ilham Ilham (Indonesian Civil Law Review, 2025)
The crime of gambling is a continuously evolving offense that negatively impacts the social and economic life of society. In the jurisdiction of the Gorontalo City Police (Polres Gorontalo Kota), gambling practices remain prevalent despite various law enforcement efforts. This study aims to analyze the law enforcement model against gambling crimes and identify the factors that hinder the effectiveness of law enforcement in the region. This research employs an empirical juridical method with a qualitative approach. Data were obtained through literature studies and interviews with law enforcement officers and local communities. The analysis was conducted descriptively to illustrate the patterns of law enforcement and the challenges faced. The findings indicate that law enforcement against gambling crimes in the Gorontalo City Police jurisdiction is carried out through three main approaches: repressive, preventive, and legal counseling. Repressive actions involve direct enforcement against offenders, while preventive measures are implemented through routine patrols and monitoring of gambling activities. Additionally, legal counseling is provided to raise public awareness of the negative impacts of gambling. However, the effectiveness of law enforcement still faces several obstacles, such as weak regulations, limited resources and integrity of law enforcement officers, and a society that remains permissive toward gambling. The study concludes that a collaborative approach between the police, government agencies, non-governmental organizations, and the community is crucial in eradicating gambling crimes. Furthermore, strengthening the integrity and capacity of law enforcement officers is necessary to enhance their performance. As a recommendation, stricter regulations and continuous educational programs are needed to reduce gambling practices in society.